Keabsahan Keputusan Tata Usaha Negara yang Diterbitkan Pasca Undang-Undang Cipta Kerja - Aldy Mirozul; Taufiqurrohman Syahuri (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
This study aims to analyze the validity of State Administrative Decrees issued by State Administrative Agencies/Officials based on the Job Creation Law in order to accelerate business licensing juxtaposed with the legal requirements of a State Administrative Decree. The research used is a critical analysis with a qualitative approach involving analysis of legal documents and related literature. This study reveals that the acceleration of the issuance of business licenses based on Government Regulation Number 5 of 2021 must meet the criteria for the legal requirements of a State Administrative Decree. The results of the study are expected to provide a comprehensive picture of the risks and impacts of the issuance of business licenses on business actors and provide input in the preparation of regulations that are derived from the Job Creation Law.